Carbon footprints of forest degradation and deforestation by “Basic-Needs Populations”: A review - Francesconi, Wendy; Vanegas Cubillos, Martha Cristina; Bax, Vincent (OAE Publishing Inc., 2022)
Forest conversion caused by subsistence or “basic needs populations” is difficult to track and measure. As the dynamics of these populations change over time, their carbon footprint impacts on natural resources also change. To reduce their potential negative impacts on forest resources, it is critical to understand what underlying causes influence their livelihoods practices. A systematic review was conducted to search for common basic needs livelihoods that result in forest loss and degradation, and thus in carbon footprint changes. Livelihood activities were grouped into seven themes (animal husbandry, crop production, fishing, illegal practices, non-timber forest products, and wood harvest). Under these themes, a non-comprehensive list of 25 activities was combined with “deforestation” and “forest degradation” as search terms in Scopus and Web of ScienceTM. A two-level snowball sampling procedure was applied to the resulting screened publications. The review produced 2200 outputs, with a final sample of 101 articles and 161 basic needs communities described. The results show that wood harvesting and crop production were the most common livelihood activities engaged in by basic needs populations. Population pressure and alternative income sources were frequently mentioned as underlying causes influencing deforestation and forest degradation and likely affecting carbon footprints through land cover change. Often considered sustainable, livelihood activities by basic needs populations can become unsustainable in response to changes in contextual and socioeconomic factors. These factors are often interrelated, leading to environmental downward spirals, which increase carbon footprints through greater demands for natural resources resulting in deforestation and forest degradation.